MACanalyzeR scRNAseq analysis tool reveals PPARγHIGH/GDF15HIGH lipid-associated macrophages facilitate thermogenic expansion in BAT - Andrea Ninni; Fabio Zaccaria; Luca Verteramo; Francesca Sciarretta; Loreana Sanches Silveira; José Cesar Rosa-Neto; Simone Carotti; Lorenzo Nevi; Paolo Grumati; Satish Patel; Giulia Carrera; Alessandro Sgambato; et al. (Nature Communications)
Abstract Macrophages are key regulators of adipose tissue plasticity. Obesity impairs brown adipose tissue (BAT) function in humans, yet macrophage-mediated mechanisms remain elusive. Here, we introduce MACanalyzeR, a single-cell RNA sequencing (scRNAseq) tool designed for comprehensive monocyte/macrophage metabolic profiling. Applying MACanalyzeR to BAT from obese male murine models (db/db and HFD-fed mice), we identify lipid-associated macrophages (LAMs) with foamy characteristics. Unlike db/db BAT LAMs, those in HFD BAT correlate with thermogenic gene expression and PPAR signaling activation. A distinct PpargHIGH LAM subcluster progressively accumulates in thermogenically active BAT. Macrophage-specific Pparg depletion disrupts BAT thermogenesis, inducing a white-like phenotype and metabolic dysfunctions. Mechanistically, PpargHIGH LAMs secrete GDF15, a key regulator of BAT identity and lipid metabolism under high-energy demand. Our study establishes MACanalyzeR as a powerful tool for immunometabolic interrogation and identifies PpargHIGH LAMs as critical mediators of BAT homeostasis.